Exploring EFL Students' Listening Difficulties and Strategies in Online Learning - M FARID FUADI (Jurnal Penelitian, Pendidikan, dan Pembelajaran, 2022)
Abstract: This article aims to describe the EFL students’ listening difficulties and strategies in online learning. The researcher implemented a descriptive qualitative research method through semi-structured interviews. The data collection for this research is from five students of the English department at the University of Islam Malang through the use of voice note WhatsApp platform.The data were presented using figure and illustration. The result shows that the students have their unique way of dealing with online learning problems that they encounter. Each student also has different causing factors that influence difficulties in online listening. It is also found that not all strategies used by students are effective against the problems they encounter especially for the problems that are not under their direct authority. The researcher offer suggestion as follows: 1) For students, it is suggested to keep practicing and develop strategies in online listening that are suitable for personal needs. 2) For lecturers, it is suggested to maintain good communication in online learning with multi-directional communication to build a good online classroom environment. 3) For the other researcher, it is suggested to conduct deeper research about more specific listening strategies.Key words: online listening, difficulties, strategies.